Design of a Flexible Wasp-Inspired Tissue Transport Mechanism - de Kater, Esther P.; Sakes, Aimée; Bloemberg, Jette; Jager, David J.; Breedveld, Paul (Frontiers in Bioengineering and Biotechnology, 2021)
Tissue transport is a challenge during minimally invasive surgery (MIS) with the current suction-based instruments as the increasing length and minimisation of the outer diameter requires a higher pressure. Inspired by the wasp ovipositor, a slender and bendable organ through which eggs can be transported, a flexible transport mechanism for tissue was developed that does not require a pressure gradient. The flexible shaft of the mechanism consists of ring magnets and cables that can translate in a similar manner as the valves in the wasp ovipositor. The designed transport mechanism was able to transport 10wt% gelatine tissue phantoms with the shaft in straight and curved positions and in vertical orientation against gravity. The transport rate can be increased by increasing the rotational velocity of the cam. A rotational velocity of 25 RPM resulted in a transport rate of 0.8 mm/s and increasing the rotation velocity of the cam to 80 RPM increased the transport rate to 2.3 mm/s though the stroke efficiency decreased by increasing the rotational velocity of the cam. The transport performance of the flexible transport mechanism is promising. This means of transportation could in the future be an alternative for tissue transport during MIS.